Philosophy and the Challenge of the Environmental Crisis (KEMANUSIAAN The Asian Journal of Humanities, 2024)
The environmental crisis is an extremely complex problem for its causes are many and diverse. An effective solution to this crisis will require a concerted effort among various academic disciplines and socio-economic institutions. This kind of undertaking, however, is immensely challenging given the lack of a unifying framework that is acceptable to everyone. One preliminary step is to have a clear conception of the kinds of causes that have brought about the crisis to determine the roles the various academic disciplines and socio-economic institutions can play in the management and eventually the resolution of the crisis. This article provides one conception of how this preliminary step can be done but with a special focus on the role of philosophy. The main objective is to clarify the aspect in the management of the crisis in which philosophy can make a substantial contribution.